A novel method for deinterleaving radar signals: First‐order difference curve based on sorted TOA difference sequence - Min Xie; Chuang Zhao; Yongjun Zhao; Dexiu Hu; Zewen Wang (IET Signal Processing)
Abstract Radar signal deinterleaving is used to separate interleaved pulse streams in the electronic support measure (ESM) systems. The histogram methods based on the difference in time of arrival (TOA) are more mature in engineering applications than other methods because of their more effortless implementation. In the increasingly complex electronic battlefield, pulse repetition interval (PRI) jitter, and pulse missing are inevitable in the interleaved pulse stream. The TOA differences of pulse trains with PRI jitter distributes in multiple adjacent PRI bins, which results in the significant reduction of the corresponding histogram value. Furthermore, the histogram values of real PRIs vary with pulse missing, which indicates that the histogram lacks robustness to pulse missing. First‐order difference curve based on sorted TOA difference sequence, denoted as FDC‐DTOA, is proposed in this paper to overcome the shortcomings mentioned above. In this method, multi‐order TOA differences are calculated and then sorted in ascending order. Then, FDC‐DTOA is obtained after a first‐order backward difference operation. Finally, an adaptive threshold is applied to FDC‐DTOA to extract candidate PRIs. The simulation results show that the proposed method has remarkable robustness to pulse missing and excellent performance in deinterleaving the pulse stream with PRI jitter.